Fathers’ role in sustainability of exclusive breastfeeding practice in post-cesarean-section mothers - Tri Budiati (PAGEPress Publications, 2021)
Background: The success of breastfeeding among post-cesarean-section mothers requires strong willingness and commitment, self-confidence, support from various professionals, and internal support (especially from their husband) and the belief and value of their family. Exclusive breastfeeding remains low in some cities such as in West Java, especially in post-cesarean-section mothers, who are influenced by certain factors. The purpose of this study is to identify husbands’ role and their support for post-cesarean-section mothers in exclusive breastfeeding. Design and Methods: This study used a qualitative phenomenological approach. with a combination of different data collection techniques: focus group discussion and in-depth interviews. Twelve husbands of post-cesarean-section mothers participated in this study. Data were analyzed by thematic content analysis. Results: Four themes were identified namely knowledge about exclusive breastfeeding, the role of the father during breastfeeding, the experience of the husband and the family in supporting breastfeeding, and Women’s lack of knowledge, inconvenience due to pain as the most impending factors of exclusive breastfeeding. Conclusion: Most fathers seem eager to be involved and assist their partners to give breastfeeding to their baby.  Furthermore, adequate support from family members, health care professionals, and employers can enable fathers to encourage and help their partners initiate and maintain exclusive breastfeeding. Fathers’ emotional, practical, and physical supports are also important factors that promote successful breastfeeding and enrich the experience of mothers.